DRAMA IMPLEMENTATION TO INCREASE LEARNING MOTIVATION ON ENGLISH CLUB STUDENTS SMPIP ASSALAMAH UNGARAN - Priesa Adi, Araaf Zulfan; Susilowati, Endang (English Literature Department, Faculty of Economics, Law, and Humanities, 2025)
This study aims to explore the implementation of drama as a learning medium to increase learning motivation in English language subjects among English Club students at SMP Islam Plus Assalamah Ungaran. The research is grounded in the Universal Design for Learning (UDL) theory by Rose and Mayer, which emphasizes the importance of providing accessibility and variety in delivering educational content to meet the diverse learning needs of students. The research uses a quasi-experimental design with two variable groups: the control group and the intervention group. The sampling method purposive sampling. Data were collected using a questionnaire based on the Academic Motivation Scale to measure students' motivation levels in the English subject before and after the implementation of drama as a learning medium. The expected results of this study will show an increase in students' motivation to learn English through the drama-based approach, aligned with UDL principles, and contribute to the development of more effective teaching strategies for the English subject in the school context. the results showed a significant increase in students‘ English learning motivation after the media intervention and drama project.Before being given drama media learning, English language learning motivation of English Club students, most of them were in the high category, namely 10 students (45.5%) in the intervention and control groups. indicating that using media that can accommodate all students’ learning styles can affect students' learning motivation.